Diurnal preference predicts phase differences in expression of human peripheral circadian clock genes - Ferrante, Andrew; Gellerman, David; Ay, Ahmet; Woods, Kerri; Filipowicz, Allan; Bearden, Neil; Ingram, Kristian Kenyon; Jain, Kriti (BioMed Central Ltd., 2015)
Background: Circadian rhythms play an integral role in human behavior,physiology and health. Individual differences in daily rhythms (chronotypes) can affect individual sleep-wake cycles,activity patterns and behavioral choices. Diurnal preference,the tendency towards morningness or eveningness among individuals,has been associated with interpersonal variation in circadian clock-related output measures,including body temperature,melatonin levels and clock gene mRNA in blood,oral mucosa,and dermal fibroblast cell cultures. Methods: Here we report gene expression data from two principal clock genes sampled from hair follicle cells,a peripheral circadian clock. Hair follicle cells from fourteen individuals of extreme morning or evening chronotype were sampled at three time points. RNA was extracted and quantitative PCR assays were used to measure mRNA expression patterns of two clock genes,Per3 and Nr1d2. Results: We found significant differences in clock gene expression over time between chronotype groups,independent of gender or age of participants. Extreme evening chronotypes have a delay in phase of circadian clock gene oscillation relative to extreme morning types. Variation in the molecular clockwork of chronotype groups represents nearly three-hour phase differences (Per3: 2.61 hours; Nr1d2: 3.08 hours,both: 2.86) in circadian oscillations of these clock genes. Conclusions: The measurement of gene expression from hair follicles at three time points allows for a direct,efficient method of estimating phase shifts of a peripheral circadian clock in real-life conditions. The robust phase differences in temporal expression of clock genes associated with diurnal preferences provide the framework for further studies of the molecular mechanisms and gene-by-environment interactions underlying chronotype-specific behavioral phenomena,including social jetlag. © 2015 The Author(s).
Keywords: Adult; Behavior; Circadian rhythm; Diurnal preference; Female; Gene; Gene expression; Hair follicle cell; Human; Human cell; Male; Night; Nr1d2 gene; Oscillation; Per3 gene; Polymerase chain reaction; Chronobiology; Chronotype; Circadian clock; Gene expression; 24 Ciencias de la Vida::2490 Neurociencias; ODS 5 - Igualdad de género